2022
DOI: 10.1038/s41598-022-07311-3
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of prokaryotic microorganisms in alkaline saline soil of the Qarhan Salt Lake area in the Qinghai–Tibet Plateau

Abstract: The composition of microbial communities varies considerably across ecological environments, particularly in extreme environments, where unique microorganisms are typically used as the indicators of environmental conditions. However, the ecological reasons for the differences in microbial communities remain largely unknown. Herein, we analyzed taxonomic and functional community profiles via high-throughput sequencing to determine the alkaline saline soil bacterial and archaeal communities in the Qarhan Salt La… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…The effects of salinization on plants are mainly ion toxicity and osmotic persecution [107] . In the high salt environment, the dominant phylum in the bacterial community is proteus, followed by Bacteroides , Firmicutes and Actinomycetes [108] . It is essential for prokaryotic microorganisms in a high salinity environment to participate in the nitrogen and carbon cycle through specific metabolic pathways.…”
Section: Soil Microbial Stress Responses Under Extreme Environmental ...mentioning
confidence: 99%
“…The effects of salinization on plants are mainly ion toxicity and osmotic persecution [107] . In the high salt environment, the dominant phylum in the bacterial community is proteus, followed by Bacteroides , Firmicutes and Actinomycetes [108] . It is essential for prokaryotic microorganisms in a high salinity environment to participate in the nitrogen and carbon cycle through specific metabolic pathways.…”
Section: Soil Microbial Stress Responses Under Extreme Environmental ...mentioning
confidence: 99%
“…We ob-tained sequences whose closest homologues belonged to the bacteria Wenzhouxiangella, Methylonatrum, Alcanivorax, Nitrincola, Anoxynatronum, Spirochaeta. This group of bacteria was assigned to moderate halophiles (Zhilina et al, 1996;Wang et al, 2022;Borsodi et al, 2017;Liao et al, 2020). In winter, alkaliphilic bacteria were presented by the genus Roseinatronobacter (рН opt > 9.5) (Sorokin et al, 2000).…”
Section: Taxonomic Composition Of Microbial Communitiesmentioning
confidence: 99%
“…Liu et al investigated soil microbial community diversity and richness from eight distinct landscapes on the Loess Plateau, representing forests, grassland, and agricultural lands at the position of 107°39′–109°36′ and the altitude of 415–1633 m. They found that soil fungal diversity and richness were different among samplings, which indicates that the fungal community structure can be used as a bioindicator in the Loess Plateau region [ 58 ]. In the Qarhan salt lake area of the Qinghai-Tibet Plateau, Proteobacteria and Halobacteria were dominant in soil, indicating that they can be used as bioindicators to assess the Qarhan salt lake area [ 59 ].…”
Section: Microbial Indicators In Natural Ecosystemsmentioning
confidence: 99%